2019
DOI: 10.3390/w11010100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Design Flow Rate of Water Supply Systems with Low Flow Showering Appliances

Abstract: The installation of water efficient appliances is an efficient demand-side water management measure favored by policymakers and water providers nowadays. The adoption of low flow showerheads in large and complex plumbing systems will not only contribute to a great reduction of shower water use in the whole water system, but also further influence the water supply system design. Hence, it is necessary to justify the redesign of existing water supply systems (such as the pipe size, storage tank volume, pumping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Compared with changing occupants' habits, taking one-off action (such as choosing low-flow rate shower appliances) might be easy to realize [59]. Under this circumstance, the low-flow rate water supply system designed by Zhou et al [60], the low-flow rate multi-jet spray atomizer designed by Panão and Delgado [61], or any other similar water-saving appliances could be a wise choice. Therefore, the residential facility managers are encouraged to install the low-flow showerhead in the bathrooms and assess the plumbing structures regularly to ensure they are well sealed.…”
Section: Implications and Suggestions For Residentials And Facility M...mentioning
confidence: 99%
“…Compared with changing occupants' habits, taking one-off action (such as choosing low-flow rate shower appliances) might be easy to realize [59]. Under this circumstance, the low-flow rate water supply system designed by Zhou et al [60], the low-flow rate multi-jet spray atomizer designed by Panão and Delgado [61], or any other similar water-saving appliances could be a wise choice. Therefore, the residential facility managers are encouraged to install the low-flow showerhead in the bathrooms and assess the plumbing structures regularly to ensure they are well sealed.…”
Section: Implications and Suggestions For Residentials And Facility M...mentioning
confidence: 99%
“…Additionally, previous studies have demonstrated the energy-and water-saving potentials of showering facilities in residential buildings and proposed several improvement strategies [10,17]. Similar or even greater potential for water and energy savings is expected for public showering facilities, such as swimming pools since more showerheads are installed and usually have fixed opening schedules.…”
Section: Introductionmentioning
confidence: 95%
“…The total water supply requirement criteria in most established practices are determined to meet the simultaneous maximum water demand [7,8]. Several studies have pointed out that it may not be an optimal solution because the maximum simultaneous water demand usually lasts only for a short time over the system lifetime, and the proper design of the water tank and pump efficiency can help lower the energy use [9,10]. Moreover, design practices have yet to be sufficiently concerned with public showering places, such as swimming pools.…”
Section: Introductionmentioning
confidence: 99%